2000
DOI: 10.1046/j.1365-3040.2000.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the early stages of tassel morphogenesis in maize (Zea mays L.)

Abstract: The effects of various environmental conditions on the initiation of tassel branches (NTB) and spikelet-pairs (NSP) were examined in the stress-sensitive maize inbred F53. Chilling induced the most important effect, with a dramatic decrease in both NTB and NSP, provided it was applied at the end of the vegetative phase and start of the floral transition phase. The primary cause of chilling-induced abortion of the tassel branches could be oxidative stress in the leaves, since lowering light irradiance during ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…The minimum value of daily mean air temperature in July reached near 10ºC. In the inbred lines of maize, Bechoux et al (2000) reported that the number of spikelets in plants maintained at 10ºC for 7 days at the 7.5-leaf stage, the starting period of spikelet development, decreased to one third of the control. Tranel et al (2009) also showed that the total length of tassel branches was reduced to half of the control when plants were exposed to a temperature treatment of 17/6ºC (day/night) for 7 days, during the tassel branch and spikelet initiation.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum value of daily mean air temperature in July reached near 10ºC. In the inbred lines of maize, Bechoux et al (2000) reported that the number of spikelets in plants maintained at 10ºC for 7 days at the 7.5-leaf stage, the starting period of spikelet development, decreased to one third of the control. Tranel et al (2009) also showed that the total length of tassel branches was reduced to half of the control when plants were exposed to a temperature treatment of 17/6ºC (day/night) for 7 days, during the tassel branch and spikelet initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In Kwiss, tassel length became significantly shorter when treated at 8-LS compared to the control (p = 0.013). Bechoux et al (2000). In the farmer's field, 39B29 reduced its ear yield and tassel length as reported in Hayashi et al (2015), whereas Papirika did not show such abnormalities in a same field.…”
Section: Methodsmentioning
confidence: 55%
“…Treatment simulating natural condition of 2003 such as 13 °C for 21 d is not suitable to determine the sensitive stage or extent of sensitivity, especially for large numbers of cultivars. It is required to reduce treatment duration, so a 10 °C for 7 d between 6-LS and 9-LS treatment is carried out for Exp2 in the present study (referring to Bechoux et al (2000), which reported the effect of low temperature on tassel development of maize inbred lines). The results show that the lowest RTL value was around 80 in the plants treated starting at between 7-LS and 8-LS in Papirika, 60 in plants treated at 8-LS in 39B29, and 30 in plants treated at 8-LS in Kwiss on average over 3 test years.…”
Section: Methods To Evaluate the Varietal Differencementioning
confidence: 99%
See 2 more Smart Citations